Inovasi Articulate Storyline: Tingkatkan Keterampilan UI/UX Figma dan Pembelajaran Kreatif - Khusnul Muttaqiyah; Heru Wahyu Herwanto; Didik Dwi Prasetya; Amir Rofiudin (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study aims to develop interactive learning media based on Project-Based Learning (PjBL) using Articulate Storyline to enhance students’ learning outcomes and creativity in the UI/UX Graphic Design subject using Figma at Islamic boarding school–based vocational schools. The research employed a Research and Development (R&D) method using the ADDIE model, which includes systematic stages of analysis, design, development, implementation, and evaluation. Validation by material and media experts indicated high validity, confirming that the developed media met the standards of content feasibility, visual design, navigation, and pedagogical effectiveness. The trial was conducted in three vocational schools over two learning cycles involving 169 students. The results revealed a significant improvement in learning achievement, with an average N-Gain score of 0.69 (moderate–high category). Moreover, 82.84% of students were categorized as creative and highly creative, based on fluency, flexibility, originality, and elaboration aspects. These findings confirm that integrating interactive digital media with a project-based approach effectively enhances students’ competencies, creativity, and mastery of digital design skills in vocational learning contexts.